Preparation and CO2 capture performances of KIT-6@reduced graphene oxide composites - Yilmaz, Muge Sari (SPRINGER, 2023)
The article reports on the preparation of KIT-6@reduced graphene oxide (K6@G) composite for CO2 capture. In order to have a better CO2 capture capacity of the composite, the effects of parameters such as the synthesis method, the amount of added graphene oxide, and amine modification (the type and content of amine solution) were investigated. The characterization of the composites were performed by X-ray diffraction (XRD), Fourier transform infrared (FTIR), elemental analysis, and nitrogen adsorption/desorption techniques. Following characterization and performance evaluation it was observed that all parameters have a significant effect on the CO2 capture performance. The results indicated that K6@G2-3-TA1 possessed the best CO2 adsorption capacity among the various composites. Next, CO2 adsorption analysis was applied at different adsorption temperatures and the composite displayed the highest CO2 capture capacity with 1.43 mmol/g at 100 degrees C. The composite also showed well stability and regenerability after four adsorption/desorption cycles, with an 8.5% decrease in initial capture capacity.
Keywords: Mesoporous silica; Reduced graphene oxide; CO2 Capture; Composite; Amine grafting; ADSORPTION; ADSORBENTS; NANOCOMPOSITE; SORBENTS; Chemistry; Materials Science